A Speaking Aristocracy : Transforming Public Discourse in Eighteenth-Century Connecticut - Grasso, Christopher (Book collections on Project MUSE., 1999)
Using biographical case studies and drawing on hundreds of printed and manuscript sources - including sermons, essays, speeches, letters, journals, plays, poems, and newspaper articles - Christopher Grasso elucidates the complex and changing relationships among religion, politics, law, science, and literature.